Quantum machine learning framework a novel approach for storm surge height estimation over the Bay of Bengal - A. Amasarao; P. Sunitha; K. Chandra Sekhar; K. A. Suneetha; B. Mmame (Stochastic Environmental Research and Risk Assessment, 2026)

Chandra’s surface thermophysical experiment (ChaSTE) onboard Chandrayaan 3 Lander - Nizy Mathew; K. Durga Prasad; Dinakar Prasad Vajja; V. Aasik; Fazil Mohammad; P.P. Pramod; M. Satheesh Chandran; Kiran John Antony; M. Ram Prabhu; M.B. Dhanya; Manu V. Unnithan; Shiju G. Thomas; et al. (Advances in Space Research, 2025)

Harnessing the power of genomics to develop climate-smart crop varieties: A comprehensive review - K.T. Ravikiran; R. Thribhuvan; C. Anilkumar; Jayanth Kallugudi; N.R. Prakash; Sandeep Adavi B; N.C. Sunitha; Krishnan P. Abhijith (Journal of Environmental Management, 2025)

Genetic enhancement of reproductive stage drought tolerance in RPHR-1005R and derivative rice hybrids through marker-assisted backcross breeding in rice (Oryza sativa L.) - N. Sravanraju; P. Beulah; V. Jaldhani; P. Nagaraju; A. S. HariPrasad; P. Brajendra; N. Sunitha; R. M. Sundaram; P. Senguttuvel (Molecular Biology Reports, 2024)

Role of surface and sub-surface ocean parameters on cyclonic storms over Arabian Sea in the recent decades - A. Amasarao; P. Sunitha; S. R. Rao; K. Chandra sekhar; B. Mmame (Natural Hazards, 2024)

Correction to: Impact of regenerative farming practices on soil quality and yield of cotton-sorghum system in semi arid Indian conditions - Janaki Ponnusamy; Lalid Kumar Santhy Poongavanam; Parameswari Ettiyagounder; Monicaa Murugesan; Krishnan Ramanujam; Sunitha Rangasamy; Suganthy Mariappan; Kavitha P. Shanmugam (Environmental Monitoring and Assessment, 2024)

Fabrication of CuNPs Using Schiff Base Ligand and Their Catalytic Reduction of Pharmaceutical Drugs, Fluorescence Selective Detection of Cd2+, Antimicrobial, and Antioxidant Activities - G. Suneetha; Dasari Ayodhya; K. Srikanth; P. Sunitha Manjari (Journal of Fluorescence, 2024)

Impact of regenerative farming practices on soil quality and yield of cotton-sorghum system in semi arid Indian conditions - Janaki Ponnusamy; Lalid Kumar Santhy Poongavanam; Parameswari Ettiyagounder; Monicaa Murugesan; Krishnan Ramanujam; Sunitha Rangasamy; Suganthy Mariappan; Kavitha P. Shanmugam (Environmental Monitoring and Assessment, 2024)

Delineation of groundwater potential zones using GIS and AHP techniques in Coimbatore district, South India - K. P. Kom; B. Gurugnanam; V. Sunitha (International Journal of Energy and Water Resources, 2024)

Unveiling the Radiative Electron-Hole Recombination of MoS2 Nanostructures at Extreme pH Conditions - Nayana K.; Sunitha A. P. (Journal of Fluorescence, 2024)

Focused identification of germplasm strategy (FIGS): a strategic approach for trait-enhanced pre-breeding - N. C. Sunitha; M. D. Prathibha; R. Thribhuvan; B. M. Lokeshkumar; P. S. Basavaraj; H. C. Lohithaswa; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

Simultaneous AC/DC distribution for the sustainable operation of smart building clusters in hybrid urban microgrids - T.P. Vishnu; Gopakumar P; Sunitha R (Energy and Buildings, 2023)

Assessment of CMIP6 model performance in simulating atmospheric aerosol and precipitation over Africa - B. Mmame; P. Sunitha; K. Samatha; S.R. Rao; P. Satish; A. Amasarao; K. Chandra Sekhar (Advances in Space Research, 2023)

Familial idiopathic intracranial hypertension: a unique and rare entity with dramatic response to weight reduction - Sachin Sureshbabu; Sunitha Mathew; Merisin Joseph; Sujith Janardhanan; Sudhir Peter; Sobhana Chindripu; Noufal Basheer; K. P. Abdurehiman (Acta Neurologica Belgica, 2022)

Metabolite Effect on Angiogenesis: Insights from Transcriptome Analysis - P. Sunitha; Kesavan R. Arya; Achuthsankar S. Nair; Oommen V. Oommen; Perumana R. Sudhakaran (Cell Biochemistry and Biophysics, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Discovery of genomic regions associated with resistance to late wilt disease caused by Harpophora maydis (Samra, Sabet and Hing) in maize (Zea mays L.) - N. C. Sunitha; E. Gangappa; R. P. Veeresh Gowda; S. Ramesh; Sunil Biradar; Dharanendra Swamy; H. B. Hemareddy (Journal of Applied Genetics, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Impact of climate change on the yield of tropical root and tuber crops vs. rice and potato in India - Raji Pushpalatha; VS Santhosh Mithra; S Sunitha; James Goerge; M Nedunchezhiyan; K Mamatha; P Ashok; Sheriful Alam; BK Saud; J Tarafdar; Surajit Mitra; Chandra Deo; et al. (Food Security, 2022)

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

Racial Health Disparity and COVID-19 - Santosh Kumar; Prashant Kumar; Sunitha Kodidela; Benjamin Duhart; Alina Cernasev; Anantha Nookala; Asit Kumar; Udai P. Singh; John Bissler (Journal of Neuroimmune Pharmacology, 2021)

GAMUT: A genomics big data management tool - E P Ramakrishnan; Saurabh Gupta; Renu Gadhari; Neeraj Bharti; Sandeep Malviya; Sunitha Manjari Kasibhatla; Jan Kim; Rajendra Joshi (Journal of Biosciences, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Are genotypes’ single-year YREMs and BLUPs good predictors of their performance in future years? An empirical analysis in dolichos bean [Lablab purpureus (L.) Sweet var. Lignosus] - V. Spoorthi; S. Ramesh; N. C. Sunitha; P. V. Vaijayanthi (Genetic Resources and Crop Evolution, 2021)

Population genomics of dengue virus serotype 4: insights into genetic structure and evolution - Vaishali P. Waman; Sunitha Manjari Kasibhatla; Mohan M. Kale; Urmila Kulkarni-Kale (Archives of Virology, 2016)

Compartmentalization of cyclic nucleotide signaling: a question of when, where, and why? - Kavisha Arora; Chandrima Sinha; Weiqiang Zhang; Aixia Ren; Chang Suk Moon; Sunitha Yarlagadda; Anjaparavanda P. Naren (Pflügers Archiv - European Journal of Physiology, 2013)

Ionic liquids as a reaction medium for lipase-catalyzed methanolysis of sunflower oil - S. Sunitha; S. Kanjilal; P. S. Reddy; R. B. N. Prasad (Biotechnology Letters, 2007)